Volume 2A: Turbomachinery 2019
DOI: 10.1115/gt2019-91227
|View full text |Cite
|
Sign up to set email alerts
|

Deficiencies in Turbulence Modelling for the Prediction of the Stability Boundary in Highly Loaded Compressors

Abstract: Reynolds-averaged Navier-Stokes (RANS) equations are employed for aerodynamic and aeroelastic modelling in axial compressors. Their solutions are highly dependent on the turbulence models for closure. The main objective of this work is to assess the widely used Spalart-Allmaras model’s suitability for compressor flows. For this purpose, an extensive investigation of the sources of uncertainties in a high-speed multi-stage compressor rig was carried out. The grid resolution near the casing end wall, which affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The parameters in Spalart-Allmaras have been adjusted on previous fans to get good agreement near the stability limit; the parameters are held constant in all the present work. Some recent publications regarding the improvements can be found in Lee et al (2018) and Moreno et al (2019). The resulting CFD code has been used over the past 20 years for flows at off-design conditions with a good degree of success; see, for example, Vahdati et al (2011), Choi et al (2012) and Dodds and Vahdati (2015).…”
Section: Flow Solvermentioning
confidence: 99%
“…The parameters in Spalart-Allmaras have been adjusted on previous fans to get good agreement near the stability limit; the parameters are held constant in all the present work. Some recent publications regarding the improvements can be found in Lee et al (2018) and Moreno et al (2019). The resulting CFD code has been used over the past 20 years for flows at off-design conditions with a good degree of success; see, for example, Vahdati et al (2011), Choi et al (2012) and Dodds and Vahdati (2015).…”
Section: Flow Solvermentioning
confidence: 99%
“…The parameters in Spalart-Allmaras have been adjusted on previous fans to get good agreement near the stability limit; the parameters are held constant in all the present work. Some recent publications regarding the improvements can be found in Lee et al (2018) and Moreno et al (2019). The resulting CFD code has been used over the past 20 years for flows at off-design conditions with a good degree of success; see, for example, Vahdati et al (2011), Choi et al (2013) and Dodds and Vahdati (2015).…”
Section: Flow Solvermentioning
confidence: 99%
“…They found that the SST turbulence model was better at predicting the stall region while the SST−CC turbulence model was better at predicting the compressor machine performance curve. Using the Spalart-Allmaras turbulence model, Moreno et al [12] carried out numerical simulations on an axial compressor and assessed the variables influencing the numerical results. It was shown that the destruction term in the SA model can have an impact on the stall margin loss.…”
Section: Introductionmentioning
confidence: 99%